Effect of changing extracellular levels of magnesium on spontaneous activity and glutamate release in the mouse neocortical slice. - Smith, D. A. (1989)
1. The mouse neocortical slice preparation, maintained in a two compartment, grease gap bath, exhibits spontaneous depolarizing activity (with or without rhythmic after potentials) after perfusion with magnesium-free artificial cerebrospinal fluid. 2. If the magnesium concentration is decrementally lowered over an extended time period, then incrementally raised following a similar time course, the spontaneous depolarizing shift activity shows a hysteresis (with regard to both frequency and amplitude), the depolarizing shifts being more resistant to magnesium during the incremental period. 3. The amino acid content of the perfusing fluid was analysed by high performance liquid chromatography (h.p.l.c.). Although a basal efflux of 6 amino acids was quantifiable, only glutamate levels increased following superfusion of the preparation with magnesium-free, artificial cerebrospinal fluid. 4. Glutamate release increased to 266% of the resting release in the presence of magnesium within the first 12 min of the change into magnesium-free artificial cerebrospinal fluid. This increase in release preceded the onset of spontaneous depolarising activity. The release of glutamate remained elevated at 182% of control up to 60 min after perfusion with magnesium-free buffer, when depolarizing activity was well established. 5. A model is presented and discussed for the genesis and maintenance of the spontaneous depolarizing shifts. It is suggested that the maintenance of this spontaneous activity reflects a long term enhancement of neocortical neurone excitability which may be related to long term potentiation in the hippocampus.